Calling site selection by the bromeliad-dwelling treefrog Phyllodytes melanomystax (Amphibia: Anura: Hylidae) in a coastal sand dune habitat. (3rd May 2016) - Cunha, Maria Silva; Napoli, Marcelo Felgueiras
ABSTRACT: We studied bromeliad selection by calling males of Phyllodytes melanomystax . The study site was a restinga environment in the northeastern state of Bahia, northeastern Brazil. We sampled 202 bromeliads, 101 with and 101 without calling males. We used multiple logistic regression analysis and Wald test to identify which of nine environmental variables investigated could explain the occurrence of calling males within bromeliads. The presence/absence of calling males in bromeliads was influenced by the number of bromeliads in a 2 m radius and the amount of debris inside the rosettes, while physical variables of bromeliads and the volume of stored water inside their rosettes had no influence. The mark-recapture procedure of P. melanomystax revealed site fidelity. This study is the first to explain the pattern of bromeliad selection by a species of the bromeliad-dwelling frog genus Phyllodytes .